Comparative study of image enhancement techniques using histogram equalization on degraded images - Arora, Shalika; Agarwal, Megha; kumar, Veepin; Gupta, Divya (International Journal of Engineering and Technology, 2018)
Image Enhancement technique plays a vital role in digital image processing for making an image to be useful for various applications. This technique is used to improve the quality of degraded images.Usually, the degradation is not evenly spread throughout the image, but most of the time it varies from region to region. Our aim is to first identify the region where enhancement is required and improve that region without disturbing its neighbourhood which does not require any improvement.Â